Manajemen Sarana Prasarana Dalam Meningkatkan Prestasi Peserta Didik Di SMA Negeri 3 Yogyakarta - Ata Ratu, Agnestia Medelin Rambu; Sunarto, Sunarto (Media Manajemen Pendidikan, 2024)
This research was conducted with the objectives of: (1) To obtain an analysis of infrastructure management planning at SMAN 3 Yogyakarta in improving student achievement; (2) To obtain an analysis of the organization of infrastructure at SMAN 3 Yogyakarta in improving student achievement; (3) To obtain an analysis of the implementation of infrastructure at SMAN 3 Yogyakarta in improving student achievement; (4) To obtain an analysis of the supervision of infrastructure at SMAN 3 Yogyakarta in improving student achievement; (5) To find out the supporting and inhibiting factors in the infrastructure management process in improving student achievement. This type of research uses descriptive qualitative methods using data collection techniques in the form of interviews, observation, and documentation. Sources of data in the study consisted of school principals, vice principals for infrastructure, vice principals for student affairs, assistant treasurer for infrastructure, school inventory, school infrastructure maintenance coordinator, teachers, and students. The data obtained were analyzed using the Miles and Huberman models with the stages of data collection, data reduction, data presentation, and conclusions. Based on the results of data analysis, it was obtained (1) Planning for SMAN 3 Yogyakarta involved several strategies, involving various parties, and this school had sources of funds from various sources (2) Organizing carried out at SMAN 3 Yogyakarta was carried out to coordinate the components involved in managing infrastructure facilities (3) The implementation of facilities is manifested in procurement, inventory using the DIY Provincial Government E-Inventory application and the DIY Provincial Government Asset Management Information System, utilization of infrastructure using an application developed by schools, namely padmanaba smart service, maintenance of infrastructure and removal of infrastructure. (4) Monitoring of infrastructure facilities at SMAN 3 Yogyakarta is carried out to control the overall management of infrastructure facilities (5) SMAN 3 Yogyakarta obtains financial support from various parties. Several obstacles were encountered in the form of inadequate storage capacity for infrastructure facilities, high prices for infrastructure needs, and negotiations for school committee approval.